2012
DOI: 10.7124/bc.00002f
|View full text |Cite
|
Sign up to set email alerts
|

Cobaltand nickel-containing enzyme constructs from the sequences of methanogens

Abstract: The conserved domain of sequences revealed in methanogens is considered for designing enzymes among which the attention has been focused on the metalloenzymes showing evolutionary significances. Methods. Molecular evolution, molecular modelling and molecular docking methods. Results. Molecular evolutionary hypothesis has been applied for designing cobalt-containing sirohydrocholine cobalt chelatase and nickel-containing coenzyme F 420 non-reducing hydrogenase from conserved domains encompassing metal-and subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ilyina et al have already demonstrated successfully the important role of artificially synthesized conservative amino acids in the principles of catalytic polypeptide properties by experimental evidence [3]. Molecular evolution-directed approach has already been reported for designing constructs of β-methylaspartate mutase from the sequences of H. marismortui [39], formyltetrahydrofolate ligase from Haloquadratum walsbyi DSM 16790 [40], sirohydrocholine cobalt chelatase and coenzyme F 420 non-reducing hydrogenase from methanogens [41][42]. Since, the evolutionary conservation in sequence as well as structure would make a major contribution in enzyme catalysis so that such conserved amino acid residues are accounted for designing enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Ilyina et al have already demonstrated successfully the important role of artificially synthesized conservative amino acids in the principles of catalytic polypeptide properties by experimental evidence [3]. Molecular evolution-directed approach has already been reported for designing constructs of β-methylaspartate mutase from the sequences of H. marismortui [39], formyltetrahydrofolate ligase from Haloquadratum walsbyi DSM 16790 [40], sirohydrocholine cobalt chelatase and coenzyme F 420 non-reducing hydrogenase from methanogens [41][42]. Since, the evolutionary conservation in sequence as well as structure would make a major contribution in enzyme catalysis so that such conserved amino acid residues are accounted for designing enzyme.…”
Section: Discussionmentioning
confidence: 99%